SEVERITY OF BURNING (Pyricularia oryzae Cav.) ON F1 RICE GERMPLASM IN THE CENTRAL ZONE IN ECUADORIAN COAST REGION - Garcés Fiallos, Felipe Rafael (2013)
Abstract The rice (Oryzaesativa L.) is the main food source in Ecuador. It is mainly a part of the staple diet of people from coast region. The disease called blast or burning rice caused by Pyricularia oryzae Cav., is among adverse biotic factors to the culture. It can cause damage from 59.6% to 100%. The objective of this research was to quantify the severity (numbers of lesions per leaf) in 39 materials (lines and varieties) in small and medium size of rice. Both of them were divided into two experiments established in central zone on ecuadorian region. The severity of rice blast was assessed on leaves of the lower, middle and superior strata in plants of rice, once by week, totaling eight times. It was used an experimental design at random complete blocks (RCB) with 3 replications. The values obtained were joined in the Area under progress curve on rice blast (AUPCRB). It was used "T" test at 5% probability of error for comparison between treatments means. There was differential health behavior between genotypes assessed in both experiments. Outstanding materials in the first experiment were the variety INIAP-16 (9.9) and the lines INIAP-14-7 (11.2) while in the second experiment were the variety Caluma (17.4) and the line CC-05-27 (18.8) for having obtained a least AUPCRB.